Implementation of Project Management in Waste Management Based on 3 R (Reduce, Reuse, Recycle) - Handoko, Wahyu Tri; Prabantoro, Gatot; Faruqi, Faris (Entrepreneurship and Community Development, 2025)
The purpose of this project is to develop a sustainable waste management system at SMP Fikri Junior High School (SMP) Jakarta by introducing recycling, reuse, and active involvement from all school components. The project follows a five-phase Project Management approach: Initiation to define goals based on 3R principles (Reduce, Reuse, Recycle); Planning for resource and activity design; Implementation, including waste sorting and awareness campaigns; Monitoring to track progress and gather feedback; and Closure to evaluate outcomes and propose long-term strategies. Key results include improved operational systems for waste handling, enhanced environmental awareness among students, teachers, and staff, and the creation of a sustainable waste management model. The project promoted hands-on learning about 3R practices, increased efficiency in managing school waste, and encouraged community-wide participation. As a result, the school environment became cleaner, healthier, and more environmentally friendly. Despite initial challenges, these were addressed through consistent education and recycling efforts, leading to a lasting impact on school culture and environmental responsibility.